THE DIVERGENCES OF ORGANIC CHARACTERISTICS OF SOURCE WATERS FROM FS AND CCL WATER TREATMENT AND ITS REMOVAL BY ALUM - Cao, Jing; Chen, Lih; Chiu, Chun; Ciou, Jian; Huang, Yu; Lai, Wen (MATTER: International Journal of Science and Technology, 2016)
Few papers were well discussed about whether the variation of organic property and initial turbidity could affect its removal by coagulation. In this study, EEFMs(Excitation Emission Fluorescent matrix) of DOM (Dissolved organic matter) by parallel factor analysis (PARAFAC) was applied to elucidate the variation of organic matter in both source waters of FS and CCL water treatments. Meanwhile, the molecular weight cut-offs was measured by HPLC equipped with Diode Array Detector (DAD) containing of HPSEC column. Current finding reveals that both source waters containing of four major fluorescent components were varied with the change of seasons. MWCOs were also affected by the change of low flow and flooding season. The optimal alum dosage was simultaneously affected by the initial turbidity as well as organic characteristic. Interestingly, the aggregation of lower or higher MWCOs was found in high alum dosage added.